Discrimination against JAI Parakansalak, Sukabumi Regency (A Study on the Obstacles to Freedom of Religion in the Context of MUI Fatwa and SKB 3 Minister) - Rohman, Hizqil Fadl; Muliadi, Muliadi; Busro, Busro (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2025)
Jemaat Ahmadiyah Indonesia (JAI) in Parakansalak, Sukabumi District, has faced various forms of discrimination and violence since the issuance of the Joint Ministerial Decree and MUI fatwa that reinforced the negative stigma against this group. This research aims to understand the discrimination experienced by the Parakansalak Ahmadiyah Congregation. A qualitative approach with descriptive method was used in this research, with data obtained through in-depth interviews, direct observation, and literature review. The results showed that the Parakansalak Ahmadiyah congregation experienced discrimination through social structures and policies that created systemic injustice. This research shows that discrimination against the Parakansalak Ahmadiyya Congregation occurs in the form of physical, administrative, and educational access barriers. This discrimination is driven by a combination of MUI fatwa, administrative policies such as SKB 3 Minister, and social pressure from the majority community. The implications of this research include the importance of interfaith dialogue and inclusive protection policies for religious minorities to ensure their rights remain protected without compromising their identity.